A service development model for public hospitals in Thailand characterized by Muslim practices - Hasan Akrim Dongnadeng,; Wisuttinee Taneerat, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Public hospitals are important agencies in the provision of public services. Upon considering the diversity of the people and the ability to provide appropriate services, human security can be realized. This research aims to study the development model of services among public hospitals attributed to Muslim practices. It is developed as qualitative research relatively collecting data through the optimization of in-depth interviews, document revision, and observation. The data is analyzed by applying the method of thematic analysis and content analysis. As for the result, it depicts that the model hospital has performed the service development of public hospitals attributed to Muslim practices, covering four key aspects. In terms of religious practices, the hospital offers relevant services to newborns, Muslim youth, prayer venue establishment, the provision during the fasting month, and terminal patients. When it comes to the provision of Halal food, a specific department is set up together with the preparation of responsible personnel. In parallel, the environment and venue for Halal food preparation are in control. The control also implies Halal process in raw material selection, logistics, production, and delivery process in addition to canteen service. In terms of patient gowns, the hospital prepares patients with the hospital gowns and grants permission to wear the hijab during a hospital stay. In relation to patient contacts, some guidelines are put in place to guide physicians when treating patients of the opposite gender.